Electronic Word Of Mouth And User Generated Content: Their Impact On The Purchase Of UMKM Products On The Marketplace - Marlina, Asti (Moneter: Jurnal Keuangan dan Perbankan, 2024)
It is impossible to deny the significance of electronic or digital commerce. This development also poses a concern for MSME actors in the marketing of their products. The marketplace is one method of marketing MSME products. Electronic Word of Mouth (EWOM) and User Generated Content (UGC) have garnered significant attention as factors that influence the purchasing behavior of online consumers, as they both have the potential to significantly impact purchasing decisions. After conducting research using SMART-PLS, it was determined that User Generated Content and Electronic Word of Mouth jointly have a substantial impact on online shopping for MSME products in the marketplace. This, in turn, can positively influence consumer decisions regarding their purchase.